Bladder dysfunction in multiple sclerosis: reeducation and technical aids - Moreno Morales, N; Pineda Galan, C; Pineda Galan, C; Arrabal Conejo, M C; Diaz Mohedo, E; Armenta Peinado, J A; Labajos Manzanares, M T (Cuestiones de Fisioterapia, 2000)
At present work we analyse, at the first time, the vesical dysfunction symptom's characteristics to sclerosis multiple's the sick. We study too the incidence of this symptom, frequency for sex, types of urinary alteration, urologic clinical more frequent... At the second time, we propose some solutions to this problem. We use the advances technologi¬al of present day for to prevent or to relieve the problems produced for urine's involuntary losses.e discuss about the wide arsenal for perineal reeducation in Physical Therapy, for either to find a so¬ution to the problem or to increase the quality of these patient's life. With everything it's sought to help it to the sick person to not only confront the «nightmare» that supposes an urine's involuntary losses, with their repercussions doctors but also, social and hygienic.